Levels of Serum Lipid profile and Kidney Function Tests in Iraqi Hypertensive Patients: Duration Effect Study - Baghdad Science Journal (مجلة بغداد للعلوم, 2017)
Hypertension is one of the leading causes of the global burden of disease, which causes serious health problems. The aim of this study is to investigate the lipid profile levels in sera of Iraqi hypertensive patients by measuring Total cholesterol (TC), triglyceride (TG) and low density lipoproteins (LDL) and kidney function levels by measuring uric acid, urea and creatinine. Seventy five individuals of Iraqi adults (Males) were divided into three groups: 25 hypertensive patients with duration of disease (1-10) year (group 1), 25 hypertensive patients with duration of disease (11-30) year (group 2) and 25 normal individuals as control group (group3). The findings indicate that serum (TC, TG and LDL) levels were significantly elevated (p ? 0.05) compared with healthy group and the values of them were significantly higher in group 2 than in group 1.This study also shows significant positive correlations between TC and TG, LDL (p ?0.01), (p ? 0.05)respectively. From collected data, a significant increase was found in the mean value of serum uric acid, urea and creatinine in hypertensive patients in two groups (1, 2) compared with control group and the levels of them were significantly higher in group2 than in group1 (p?0.01).The results also indicate strong correlations between parameters studied of kidney function tests ( p? 0.01). This study has shown that lipid profile and renal function levels abnormalities are highly prevalent among Iraqi hypertensive patients and also the effect of duration of disease on parameters was studied.